Health and Food Security of International Students at a Southern University (P04-078-19) - Sandha, Prabhdeep (Curr Dev Nutr, 2019)
OBJECTIVES: To determine if health (physical functioning, role limitations due to physical health, role limitations due to emotional problems, energy/fatigue, emotional well-being, social functioning, pain, and general health) predicts Household Adult Food Security Status in international students attending a southern university. METHODS: Cross-sectional survey. A simple random sample of 750 adult international students 18 years and older from 950 attending. Participants were recruited via email and completed a Qualtrics survey (USDA 6-item food security survey module, Rand SF-36 health survey). Analysis: Ordinal Logistic Regression with Proportional Odds Test RESULTS: Participants (n = 94, 12.5% response rate) were primarily male (n = 48/94, 51%), from 35 different countries, and living in households characterized by high (n = 27, 28.7%), marginal (n = 12, 12.8%), low (n = 24 (25.5%), and very low (n = 31, 33.0%) food security. There were proportional odds, as assessed by a full likelihood ratio test, comparing the fitted model to a model with varying location parameters, [χ(2)(16) = 6.87, P = .976]. The final model significantly predicted the dependent variable over and above the intercept-only model [χ(2)(8) = 31.10, P < .001] and explains 37.1% of the total variance. Only social functioning (odds ratio, 0.95; P = .002) and general health (odds ratio, 0.96; P = .017) significantly predicted the odds of living in a food secure household. As such, there were decreased odds of living in a food insecure household for individuals with good social functioning and general health. CONCLUSIONS: Better social functioning and general health decrease the likelihood of international students living in a food insecure households, warranting further exploration. FUNDING SOURCES: N/A.